Sustainability of Rural Road Development: A Case Study on Woro Village Kepohbaru District Bojonegoro Region - Lestari, Puji; Rachmansyah, Arief; Efani, Anthon; Pertiwi, Maharani (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
Road development has been a primary focus in efforts to enhance connectivity and mobility across various regions, especially in densely populated urban areas that often serve as economic hubs. While crucial for addressing mobility challenges in urban settings, it is essential to acknowledge that road development in rural areas also holds significant importance. This paper investigates the sustainability of rural road development through five dimensions of environmental, social, economic, institutional management, and law enforcement, a case study on Woro Village, Kepohbaru District, Bojonegoro Region. The quantitative research collected data through a questionnaire from 84 respondents who are members of the village community. The data analysis employed Multidimensional Scaling (MDS) using R-studio software. The result is indicated by the sustainability index of the environmental index of 83.93; the social index of 86.46; the economic index of 88.06; the institutional management index of 79.32 and the law enforcement index of 86.15. The research findings indicate rural road development has demonstrated good sustainability in various aspects, including environmental, social, economic, management institutions, and law enforcement. This confirms that efforts to build rural roads have provided sustainable and diverse positive impacts on local communities and the surrounding environment.